Efeito do Ranibizumabe e do a Amfenac nas habilidades funcionais em células de melanoma uveal - Bravo Filho, Vasco Torres Fernandes [UNIFESP] (2018)
Objective: To evaluate the effects of ranibizumab and amfenac in human uveal melanoma (UM) cell lines and to explore the ability of these compounds to sensitize UM cells to radiation. Methods: The 92.1 human UM cell line was cultured; the cells were then submitted to the proposed treatment (ranibizumab, amfenac, and a combination of ranibizumab/amfenac). Proliferation, migration, and invasion assays of the 92.1 UM cell lines were assessed after pretreatment with ranibizumab (125 μg/mL) or amfenac (150 nM), or the combination of both compounds. In addition, proliferation rates were assessed after treatment with ranibizumab and amfenac, and the cells were subsequently exposed to various doses of radiation (0 Gy, 4 Gy and 8 Gy). Results: Proliferation assay – cells treated with a combination of ranibizumab and amfenac had lower proliferation rates compared to controls (p=0.016) and to the group treated only with ranibizumab (p=0.033). Migration assay – a significantly lower migration rate was only observed in the group treated with amfenac relative to the control (p=0.014) and ranibizumab groups (p=0.044). Invasion assay – there were no significant differences among the studied groups. Irradiation exposure – in the 4 Gy dose group, there were no significant differences among any groups. In the 8 Gy dose group, treatment with ranibizumab, amfenac, and their combination prior to the 8 Gy radiation dose led to a marked reduction in proliferation rates (p=0.009, p=0.01 and p=0.034, respectively) compared to controls. Conclusion: The combination of ranibizumab and amfenac decreased the proliferation rate of UM cells; however, only amfenac monotherapy significantly decreased cell migration. The radiosensitivity of the 92.1 UM cell line increased following the administration of ranibizumab, amfenac, and their combination. Further investigation is warranted to determine if this treatment is a viable pretreatment strategy to render large tumors amenable to radiotherapy.